DEVELOPMENT OF METAVERSE-BASED VIRTUAL DISASTER GALLERY AS A SUPPORT SYSTEM FOR DISASTER EDUCATION IN GEOGRAPHY LEARNING - Syamsul Bachri; A.Riyan Rahman Hakiki; Sumarmi Sumarmi; Alfyananda Kurnia Putra; Tabita May Hidiyah; Nanda Regita Putri; Mellinia Regina Prastiwi (Universitas Muhammadiyah Mataram, 2024)
Abstrak: Pendidikan kebencanaan memainkan peran penting dalam menumbuhkan kesiapsiagaan bencana di kalangan pelajar. Namun, implementasi pendidikan kebencanaan di Indonesia masih memiliki keterbatasan, terutama karena kurangnya media yang interaktif dan kontekstual untuk mendukung proses pembelajaran. Penelitian ini bertujuan untuk mengembangkan Galeri Bencana Virtual Berbasis Metaverse sebagai sistem pendukung pendidikan kebencanaan dalam pembelajaran geografi. Metaverse merupakan teknologi yang mampu menciptakan dunia virtual 3D. Penelitian ini menggunakan model pengembangan 4D, yang meliputi tahapan Define, Design, Develop, dan Disseminate. Media diujicobakan kepada 33 siswa kelas XI di SMAN Pesanggaran untuk menghasilkan media pembelajaran yang layak dan efektif. Temuan penelitian menunjukkan bahwa Galeri Bencana Virtual Berbasis Metaverse sangat valid dan efektif sebagai sistem pendukung pendidikan untuk pendidikan kebencanaan. Temuan ini menunjukkan bahwa mengintegrasikan teknologi VR dalam pendidikan kebencanaan dapat menjadi referensi yang berharga untuk mengembangkan media pendidikan yang inovatif di masa depan. Abstract: Disaster education plays a crucial role in fostering disaster preparedness among students. However, the implementation of disaster education in Indonesia faces limitations, particularly due to the lack of interactive and contextual media to support the learning process. This study aims to develop a Metaverse-Based Virtual Disaster Gallery as a support system for disaster education in geography learning. The metaverse is a technology capable of creating a 3D virtual world. This research employs the 4D development model, which includes the stages of Define, Design, Develop, and Disseminate. The media was tested on 33 eleventh-grade students at SMAN Pesanggaran to produce a feasible and effective educational tool. The research findings demonstrate that the Metaverse-Based Virtual Disaster Gallery is highly valid and effective as an educational support system for disaster education. These findings suggest that integrating VR technology in disaster education can serve as a valuable reference for developing innovative educational media in the future.